Study of the prevalence of bovine tuberculosis in Govuro District, Inhambane Province, Mozambique - Godfroid, Jacques (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Tropical Diseases))--University of Pretoria, 2009.